WORLD EXPERIENCE OF BUSINESS PROCESSES ORGANIZATION BUILD-INVESTMENT PROJECTS NEW FORMS AND MANAGEMENT IN THE FIELD OF UKRAINE COMPLEX OBJECTS DEVELOPMENT - Redkin, O. V.; Pahomov, R. I.; Zyma, O. E. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The scientific principles and practical recommendations on the organization and management of business processes and construction investment projects in the real sector of the Ukrainian economy are developed. These issues are considered on an example of the development of objects and processes in the oil and gas complex. The basis of its improvement is proposed to apply new forms and best international experience to ensure the modern progress and competitiveness of complex industrial and business systems. It is determined that the practical recommendations given in the article can be successfully applied in industry and other sectors of the real economy sector of Ukraine. Their use should ensure the acceleration of modern progress and the growth of the competitiveness of the domestic economy.